Conceiving a feasible degradation model of polylactic acid-based composites through hydrolysis study to polylactic acid/wood flour/polymethyl methacrylate. (8th September 2019) - Wan, Lu; Li, Changxin; Sun, Ce; Zhou, Shuai; Zhang, Yanhua
Abstract: On the road of wide popularization and application of polylactic acid (PLA), its degradation performance frequently fetters the advancing feet. The work attempted to develop a (PLA & Coating-layer) @Filler [(PLA&C)@F ] model composite with high-effective degradation property in order to clear the obstacles for the promotion of PLA-based-materials products and alleviate the environmental burden. Firstly, PLA/wood flour/polymethyl methacrylate composite was fabricated by melt blending PLA, wood flour and polymethyl methacrylate, and (PLA & polymethyl methacrylate) @wood flour as a demonstration model was established. Then, the degradation rate of PLA/wood flour/polymethyl methacrylate and neat PLA was evaluated by hydrolysis test. The composite of (PLA & polymethyl methacrylate) @wood flour demonstration model achieved satisfying result, its hydrolysis rate was 8.56 times faster than that of neat PLA under the same conditions. The reasons were attained through various testing methods. Lastly, the characterization of Fourier Transform Infrared Spectroscopy (FTIR), the test of differential scanning calorimetry (DSC), and the observation of scanning electron microscope (SEM) to the materials in predetermined stages were applied to determine significant pieces of real-time information. By combining various information to provide right characterization for studying super-fast hydrolysis mechanism of PLA/wood flour/polymethyl methacrylate. The development of (PLA & Coating-layer) @Filler [PLA&C)@F ] model is a significant work both accelerating research and even controllable exploration of PLA-based composite degradation.